Validity and reliability of a handheld blood glucose monitor during exercise and an oral glucose tolerance test - Granderson, Davoncie M. (Array, 2019)
The purpose of the present study was to examine the validity and reliability of the handheld Nova Max Plus blood glucose monitor during an oral glucose tolerance test and 60-minute bout of exercise. Thirty subjects (mean age±SD=22.3±1.9 years; body mass=77.6±14.2 kg) volunteered for an oral glucose tolerance test or 60-minute treadmill test. Blood glucose concentrations were measured from the fingertip at six time points during both tests. The reference method of blood glucose analysis was the Yellow Springs Instruments (YSI) 2300. Our results indicated that the blood glucose values provided by the Nova Max Plus were significantly (p<.05) greater than the YSI 2300 at all-time points of the oral glucose tolerance test and treadmill test. In addition, the Nova Max Plus exhibited an overall mean absolute relative deviation (±SD) of 9.0 (±7.0) and did not meet the 95% accuracy requirements of ISO 15197:2013. The Bland-Altman plot for constant error (YSI 2300 – Nova Max Plus) versus the reference method (YSI 2300) indicated an average negative bias (-8.2 mg·dL-1) that increased (r=-0.23) at higher blood glucose values. Intra-device reliability analyses for the Nova Max Plus demonstrated the ICC was R=0.99 and CV=3.0%, with no mean differences between the test and retest values. These findings suggested that the Nova Max Plus provided highly reliable, yet inaccurate blood glucose values compared to the YSI 2300 during the dynamic conditions associated with an oral glucose tolerance test and exercise.